Return of State Assets Through Civil Lawsuits in Corruption Criminal Action - Dewi, Atika Sandra; Asrul, Asrul (Budapest International Research and Critics University, 2019)
The main problem to be examined is how the efforts of prosecutors as state lawyers in returning assets of state assets resulting from criminal acts of corruption through civil lawsuits and to find out the constraints in returning those assets. In this study the authors use the Normative Law research method, the Normative Law research method or the library research method is a study that studies study documents using various secondary data in the form of positive rules or norms in the legislation system. It can be concluded that the actions of the Prosecutors as investigators and public prosecutors obtained the fact that there has been a real loss of state finances and acts against the law so that it will facilitate the State Attorney in carrying out civil lawsuits. it can even be known from the beginning of the investigation that suspects, defendants and convicts possess property to recover state financial losses incurred, by preparing formal evidence and arguments known as the burden of proof in order to achieve the goal of returning state assets through civil lawsuits in criminal offenses corruption. In the process of returning assets resulting from criminal acts of corruption experienced several obstacles that were quite difficult for law enforcement officials in the process of efforts to recover state assets resulting from these criminal acts of corruption, among those obstacles were systemic corruption, abuse of power (Abuse of Power) and transformation of national law.